FETCH data, 22-23 March, 1998 - Sahlée, Erik (Uppsala University, 2018)
The FETCH (Flux, État de la mer et Télédétection en Condition de fetch variable, or Flux, sea state, and remote sensing in conditions of variable fetch) experiment took place from 12 March to 16 April 1998 in the Gulf of Lion, Mediterranean Sea.

One of the goals of FETCH was to improve the parameterization of turbulent fluxes of momentum and heat with particular emphasis on fetch-limited situations and high wind conditions. During FETCH, fluxes were measured from three platforms. Momentum flux was measured by eddy correlation from a moored Air-Sea Interaction Spar (ASIS) buoy; momentum, heat and humidity fluxes were measured using the inertial dissipation method from the ship N.O. L'Atalante; eddy correlation fluxes were measured on a few occasions from an aircraft.

See more detailed information on data in linked publications.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för beskrivning av data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
FETCH data, 22-23 March, 1998
Keywords: wind; vind; oceanography; oceanografi; seas; hav; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser